A SOCIOLINGUISTIC STUDY OF NICKNAMES AND ITS APPLICATION AMONG THE STUDENTS OF BACHA KHAN UNIVERSITY CHARSADDA - Saeed Ur Rahman; Taimur Ali Shah; Syed Muhammad Saadan Kaka Khel; Syed Asad Ullah Jan; Pir Attiq Ur Rahman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The research study focuses on finding the practised area for nicknames among the students of Bacha Khan University Charsadda. It aims at finding the differences and the ratio between the male and female students with reference to nicknames. The study is interesting since the culture of nicknames is exercised and rehearsed among the students of the aforementioned university. The research is both qualitative and quantitative. The survey and analysis reveal that female students are more concerned about each other whereas male are incautious. Moreover, female are more cooperative than male when filling or answering the questionnaire. The study analyzes the answers acquired and concludes that the female practice nicknames more than male. The ratio of nickname users is more in female. The researchers have limited the study to merely four departments at Bacha Khan University Charsadda. They are: Department of English, Department of Computer Science, Department of Management Science, and Department of Botany. Taking four departments as a sample represented the university. The paper also shows that both genders tend to give nicknames covering the physical area. The nicknames female give are often positive. Contrary to that, nicknames of male cover physical area were often found negative.